Change in emotional and theory of mind processing in borderline personality disorder: a pilot study - Kramer, Ueli; Schmitt, Ruth (The journal of nervous and mental disease, 2018)
Abstract: Changes in emotional processing (EP) and in theory of mind (TOM) are central across treatment approaches for patients with borderline personality disorder (BPD). Although the assessment of EP relies on the observation of a patient's self-criticism in a two-chair dialogue, an individual's TOM